R. Mac Mullen, Roman government's response to crisis AD 257-337 - Kodrębski, Jan (Czasopismo Prawno-Historyczne, 1983)
Recenzja: Ramsay MacMullen, Roman government's response to crisis AD 257-337, New Haven and London, Yale University Press. 1978.